The Use of Quizizz as Istiqraiyah-Based Nahwu Learning Media in the Digital Age - Fadilah Al Azmi; Muassomah Muassomah; Nabila Nailil Amalia; Nur Diana (University of Darussalam Gontor, 2023)
In this Digital Era, educators are required to integrate science and technology in all aspects of learning to create effective learning and make it easier for students to understand the material; besides that, with this technology, students can easily find sources of knowledge. One of the Web Tools that are suitable for learning in this Era is Quizizz. This study aims to determine the steps of using Quizizz as an Istiqraiyah-based nahwu learning medium in the Digital Age and to analyze students' perceptions of using Quizizz as an Istiqraiyah-based nahwu learning medium in the Digital Age. This study uses a descriptive qualitative approach. The data collection technique uses documentation and questionnaires. After the data is collected, a descriptive analysis is carried out using: 1) data collection, 2) data reduction, 3) data presentation and 4) conclusion/verification. The results of this study show the steps in using Quizizz as an Istiqraiyah-based nahwu learning media as follows: a). present an example, b). instructed to analyze the example, c). conclude from the examples observed d). make examples related to the material, e). give a quiz using quizizz f). directions for doing g). monitored the results of the answers and the majority of students responded positively to using Quizizz as an Istiqraiyah-based nahwu learning medium in this Digital Age.